Linking Higher Education Management Practices and Student Learning Motivation: A Multi-Site Qualitative Study across Indonesian Provinces - Wahyu Satrio Tunggal; Ahmad Ridwan (Zabags International Journal of Education, 2026)
This study is grounded in the persistent disparity in the quality of higher education in Indonesia, which has not kept pace with its quantitative expansion, particularly in the context of regional inequalities that influence institutional management practices and student learning motivation. The primary objective of this research is to explore the relationship between higher education management practices and student learning motivation, as well as to identify contextual factors that moderate this relationship across different provinces. This study employs a qualitative approach with a multi-site strategy, utilizing in-depth interviews, focus group discussions, observations, and document analysis involving students, academic leaders, administrative staff, and policymakers. The findings indicate that participatory leadership, flexible academic policies, adequate resource distribution, and strong institutional support contribute significantly to enhancing student learning motivation, with variations influenced by regional economic conditions and infrastructure. This study contributes to the integration of motivational perspectives and higher education governance, offering practical implications for the development of more adaptive, context-sensitive, and student-centered higher education management practices.